2015
DOI: 10.1002/jso.24063
|View full text |Cite
|
Sign up to set email alerts
|

Clinical course and prognostic factors in patients with malignant pheochromocytoma and paraganglioma: A single institution experience

Abstract: Patients with malignant PCC/PG have diverse clinical courses. Poor survival was independently associated with older age and synchronous metastasis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
38
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(46 citation statements)
references
References 29 publications
2
38
2
Order By: Relevance
“…PCC and paraganglioma are benign or malignant neuroendocrine neoplasms from neural crests, with diverse clinical courses [4][5][6][7]. Worthy of note, metastases of the malignant tumors involve lymph nodes, liver, lungs and bones, where chromaffin tissue is normally absent [7].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…PCC and paraganglioma are benign or malignant neuroendocrine neoplasms from neural crests, with diverse clinical courses [4][5][6][7]. Worthy of note, metastases of the malignant tumors involve lymph nodes, liver, lungs and bones, where chromaffin tissue is normally absent [7].…”
Section: Discussionmentioning
confidence: 99%
“…Worthy of note, metastases of the malignant tumors involve lymph nodes, liver, lungs and bones, where chromaffin tissue is normally absent [7]. PCC is located in adrenal glands, whereas paragangliomas develop in paraganglia of the head, neck, thorax, abdomen and pelvis [4][5][6][7]. Differences in clinical behaviour and in prognosis, have suggested that these tumors should be considered as separate clinical conditions [4,5].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is estimated that up to 5% of patients presenting with adrenal incidentalomas are found to have pheochromocytomas. [1], [13]. Of this, only 10% are malignant pheochromocytoma characterized by the presence of metastasis which spread to organs where no chromaffin cells are present.…”
Section: Introductionmentioning
confidence: 99%